Effect of SKT-b Vibrio probiotic bacteria addition at different developmental stages on tiger shrimp Penaeus monodon larvae survival rate - . Widanarni; M.S. Arifin; . Sukenda (Jurnal Akuakultur Indonesia)
This experiment was conducted to study the effect of probiotic bacteria SKT-b Vibrio addition at different developmental stages on survival rates of tiger shrimp Penaeus monodon larva.  Main activity of this experiment consisted of tiger shrimp rearing started from nauplius stage until Pl10 and addition of 106 CFU/ml SKT-b Vibrio probiotic bacteria at various developmental stages namely at early nauplius stage, early zoea zoea stage, early mysis stage, early postlarva (Pl) stage, every developmental stage changes, everyday, and control (without probiotic bacteria addition). Results showed that survival rates of shrimp larva ranged at 24,17%-35,83% with the higest value in the treatment of probiotic bacteria addition at every developmental stage changes namely 35,83%, whereas the lowest was found at control (without probiotic bacteria addition) namely 24,17%.  No significantly different was found in term of shrimp growth rate among control and treatment. Growth rate in length of tiger shrimp larva ranged 18,64%-19,09% for SKT-b Vibrio addition and 18,47% for control.